Single Center Experience of Diarrhea Associated Hemolytic Uremic Syndrome in Pediatric Intensive Care Unit - Caner Alparslan; Mehmet Nur Talay; Murat Kanğın (Çocuk Dergisi)
Objective: Hemolytic uremic syndrome (HUS) is characterised by acute kidney injury, hemolytic anemia and thrombocytopenia. In children, it is mostly related with diarrhea (D+). In this paper, we aimed to determine clinical parameters and prognostic factors in D+HUS.Materials and Methods: This retrospective study was conducted with D+HUS 15 pediatric patients in a pediatric intensive care unit between March 2019 and August 2020. Patients demographics, initial vital signs, laboratory parameters (hemoglobine, hematocrit, white blood cell, platellets, creatinine, urea, uric acid, lactat dehydrogenase, aspartat aminotransferase, alanine aminotransferase, amilase, albumine, C3 and C4), plasma therapy, plasma exchange, RRT type and duration, and the need for blood products were evaluated. Therefore, extra-renal involvement, eculizumab treatment and last follow-up were recorded.Results: The study group consisted of 9 males (60%) and the median age was calculated as 18 months. In 60% of the patients, RRT was implemented. Peritoneal dialysis (in 5) was the most preferded dialysis method. Five patients (33%) had extra-renal involvement. Nine patients (60%) had completely recovered, therefore proteinuria, chronic kidney disease, end-stage kidney disease and neurologic sequel developed in 3 (20%), 1 (6.6%), 1 (6.6%) and 1 (6.6%), respectively. Hospitalization and oligoanuria duration had a significant impact on sequel development [Hospitalization duration: OR:1.28 (%95 CI:0.77–0.98) (p=0.04), Oligoanuria duration: OR:1.46 (%95 CI:0.94–1) (p=0.04)].Conclusion: In this study, we showed that hospitalization and oligoanuria duration had a significant impact on sequel development. We believe that there is a need for more clinical studies to delinate more precise mechanisms of the disease and eliminate worse outcomes of D+HUS.